POTENTIAL ABILITY OF THE SOLANUM-FEEDING LADYBIRD BEETLE HENOSEPILACHNA DIFFINIS (COLEOPTERA; COCCINELLIDAE) TO USE THE INTRODUCED FABACEOUS PLANT CENTROSEMA MOLLE - Shogo Kikuta; Naoyuki Fujiyama; Sih Kahono; Norio Kobayashi; Sri Hartini; Haruo Katakura (BRIN Publishing (Penerbit BRIN), 2013)
-